Conceptualizing prognostic awareness in advanced cancer: A systematic review. (September 2014) - Applebaum, Allison J; Kolva, Elissa A; Kulikowski, Julia R; Jacobs, Jordana D; DeRosa, Antonio; Lichtenthal, Wendy G; Olden, Megan E; Rosenfeld, Barry; Breitbart, William
This systematic review synthesizes the complex literature on prognostic awareness in cancer. A total of 37 studies examining cancer patients' understanding of their prognosis were included. Prognostic awareness definitions and assessment methods were inconsistent across studies. A surprisingly high percentage of patients (up to 75%) were unaware of their poor prognosis, and in several studies, even their cancer diagnosis (up to 96%), particularly in studies conducted outside of North America. This review highlights surprisingly low rates of prognostic awareness in patients with advanced cancer as well as discrepancies in prognostic awareness assessment, suggesting the need for empirically validated measures of prognostic awareness.